Aplikasi Soft System Methodology dalam Analisis Diplomasi Angkatan Laut Indonesia melalui Pengiriman Satgas Maritim TNI Pada Misi UNIFIL MTF - Sirmareza, Trio (Global: Jurnal Politik Internasional, 2017)
This article discusses Indonesia's participation in UNIFIL MTF, as a way for the country to exercise its naval diplomacy. Using Ken Booth's theory of naval diplomacy as analytical framework and employing the Soft System Methodology model, this article seeks to explain Indonesia's motives for joining UNIFIL MTF, namely the maintenance of the world peace as stipulated by the country's constitution and concomitantly, Indonesia's interest to enhance its global role as middle power. The application of naval diplomacy and Soft System Methodology in this article provides a theoretical and methodological-informed analysis in scrutinising Indonesia's participation in international peacekeeping operation. By doing so, this article attemps to fill the lacuna in the existing body of works which commonly neglect the theoretical basis and/or sound methodological framework in their observation and evaluation concerning the topic at hand. The article finds that Indonesian maritime task force in UNIFIL MTF has flexibility, mobility, projection ability and access potential to carry out Indonesia's diplomatic agenda. However, Indonesia still needs to consider improving the capacity of its maritime task force in order for it to function as maximum signifier for Indonesia's prestige and foreign policy commitment.